Large exudative retinal detachment with choroidal granuloma unmasking disseminated tuberculosis: imaging and management. Issue 3 (31st March 2021) - Sachan, Anusha; Chawla, Rohan; Lata, Suman
Abstract : A 26-year-old man presented with diminution of vision in the left eye associated with malaise and occasional mild fever. On fundus examination, the patient had left eye inferior bullous retinal detachment with choroidal granuloma. Systemic examination revealed a non-tender swelling on the right wrist. Correlating ophthalmic and systemic findings, a presumptive diagnosis of left eye exudative retinal detachment with choroidal tuberculoma and tubercular osteomyelitis of the right wrist was made. On imaging, asymptomatic multiorgan involvement was observed in the chest, abdomen and spine. The patient was started on antitubercular treatment along with peribulbar steroid. A reduction in size of exudative retinal detachment and tuberculoma with improvement in vision was noted on serial follow-ups. This case highlights the importance of thorough systemic evaluation in cases of ocular tuberculosis as the eye may not be the primary site but the early presenting feature of disseminated tuberculosis. Local posterior subtenon can be used for faster resolution of exudative retinal detachment and intraocular inflammation.